A novel direct method to determine adherence to simvastatin therapy in patients with coronary heart disease. (11th May 2021) - Vethe, N; Husebye, E; Andersen, AM; Bergan, S; Kristiansen, O; Fagerland, MW; Munkhaugen, J
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): National Association of Health OnBehalf: NORCOR Background: Poor adherence to statin therapy remains a public health concern associated with adverse clinical outcome. Reliable classification and detection of statin adherence is needed in clinical practice and for clinical studies with overall aim to improve the lipid management. Simvastatin is a frequently used statin in cardiovascular disease prevention. Purpose: To develop a feasible test based on spot blood samples to monitor the adherence to simvastatin therapy in coronary heart disease (CHD) patients. Methods: Eighteen CHD patients on an evening dose of simvastatin 20 mg (n = 7), 40 mg (n = 5) and 80 mg (n = 6) were studied at steady-state pharmacokinetics. Ten patients were instructed to avoid simvastatin dosing and return for blood sampling the subsequent three days. Dose-normalized plasma concentrations of simvastatin lactone, simvastatin acid and the sum of the two were evaluated as discriminators between adherent dosing and dose avoidance. Bioanalytical quantifications were performed with liquid chromatography tandem mass spectrometry. Results: The dose-normalized plasma concentrations at steady-state demonstrated 23-fold and 39-fold interindividual variabilities for simvastatin lactone and simvastatin acid. A simvastatin acid cut-off at 1.0·10^-2 nmol/L/mg identified 100% of those omitting 2 doses and 60% of those omitting a single dose (Figure 1). Simvastatin acid showed superior ability to discriminate dose avoidance from adherence, and also the best agreement between samples handled at ambient and cool temperature (median deviation 3.5%, interquartile range -2.5 to 13%). A cut-off for morning dose schedule, with similar ability to discriminate, was estimated at 2.0·10^-3 nmol/L/mg. Conclusion: A novel method discriminating between good and poor adherence to simvastatin therapy in CHD patients has been developed. The sample handling is feasible for routine practice, and the assessment of adherence can be performed by direct measurements in spot blood samples, according to specific cut-off values.